Public expenditure decision making: A comparative analysis - Thomas R. Cusack (Wissenschaftszentrum Berlin für Sozialforschung (WZB); Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1987)
An effort is made to draw out some of the fundamental distinctions amongst the many approaches to explaining government resource allocation behavior. The relative dominance of the environment and decision making imagery are suggested as two principal organizing dimensions. A brief survey of the literature demonstrates some of the principal themes that are apparent using this framework. Drawn from one of the many approaches, the Competing Aspiration Levels Model(CALM) is described and then applied to the recent budgetary history of twelve developed market systems. The results of the empirical analysis suggest that some features of the budgetary process in the U.S. make it quite distinctive relative to other industrialized democracies. In particular, it is shown that U.S. fiscal authorities are relatively less committed to balancing revenues and expenditures and that the military sector is more sensitive to international security calculations in the formulation of budgetary targets. Comparison of the results for the twelve countries studied also suggest little support for the hypothesis that wealth/predictability in the budgetary environment leads to greater use of incrementalist strategies. The results of the comparative analysis, however, do support the contention that the defense and civilian sectors are enmeshed in a competitive situation implying trade-offs between the two in spending levels. – – Versucht wird, die grundlegenden Unterschiede zwischen den vielen Erklärungsansätzen der Dynamik der öffentlichen Haushalte herauszuarbeiten. Die relative Dominanz der Umwelt und die Typisierung des Entscheidungsprozesses bilden die wichtigsten Bezugspunkte zur Klassifizierung dieser Erklarungsansatze. Eine kurze Ubersicht der Literatur zeigt sodann die zentralen Themen dieses Bezugsschemas auf. Das Competing Aspiration Levels Model (CALM) wird erläutert und angewandt auf die Entwicklung der öffentlichen Haushalte zwolf westlicher Industriestaaten wahrend der Periode 1955-1979. Die Ergebnisse der empirischen Analyse erlauben es, den Budgetprozeß der Vereinigten Staaten als sehr verschieden von dem der anderen Staaten zu charakterisieren. Insbesondere wird gezeigt, daß amerikanische Finanzbehörden dem Budgetausgleich weniger Gewicht beimessen, und dafür der militarische Sektor bei der Formulierung der Haushaltsziele eine höhere Reagibilitat in Bezug auf internationale Sicherheitsüberlegungen aufweist. Die vergleichende Analyse liefert zudem kaum eine Bestätigung der These, daß ein hohes Maß an Reichtum/ Vorhersehbarkeit in der haushaltspolitischen Umwelt einer gesteigerten Anwendung inkrementeller Strategien förderlich ist. Die Ergebnisse der vergleichenden Analyse unterstützen jedoch die Auffassung eines Wettbewerbes zwischen dem militärischen und zivilen Sektor, der ein inverses Verhaltnis zwischen den Ausgabenniveaus dieser beiden Bereiche begründet.
Keywords: 330